Răspuns :
Răspuns:
a) 2; b) -1; c) 4
Explicație pas cu pas:
a)
[tex] \frac{5 \times 4 + 1}{4} \div \frac{5 \times 5 - 2 \times 2}{2 \times 5} + \frac{5}{6} \div \frac{1 \times 3 + 2}{3} - 1 = \\ = \frac{21}{4} \div \frac{21}{10} + \frac{5}{6} \div \frac{5}{3} - 1 = \\ = \frac{21}{4} \times \frac{10}{21} + \frac{5}{6} \times \frac{3}{5} - 1 = \\ = \frac{5}{2} + \frac{1}{2} - 1 = \frac{6}{2} - 1 = 3 - 1 = 2[/tex]
b)
[tex]( - \frac{3}{4} + \frac{3}{4} \times \frac{2}{1} ) \times ( - \frac{1 \times 3 + 1}{3} ) = \\ = ( - \frac{3}{4} + \frac{6}{4}) \times ( - \frac{4}{3}) = \frac{6 - 3}{4} \times ( - \frac{4}{3}) = \\ = - \frac{3}{4} \times \frac{4}{3} = - 1 [/tex]
c)
[tex]{2}^{170}\div{8}^{56}+{(-2)}^{2}+ (-3)^{1}+(-1) = {2}^{170} \div {2}^{168} + 4 - 3 - 1 = {2}^{2} + 4 - 4 = 4[/tex]